2013
DOI: 10.3892/etm.2013.1429
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of lateral knee joint stability following resection of proximal fibula tumors

Abstract: Managing tumors of the proximal fibula may require en bloc resection of the fibular head with the attachment site of the lateral collateral ligament (LCL) and biceps femoris tendon. The aim of the present study was to evaluate knee stability and the Musculoskeletal Tumor Society (MSTS) functional score of patients with proximal fibula tumors. Twenty-nine patients with proximal fibula tumors were retrospectively reviewed (18 patients in the reconstruction group and 11 patients in the non-reconstruction group). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 20 publications
1
30
1
Order By: Relevance
“… 1 , 10 In contrast, iatrogenic permanent loss of peroneal nerve function is expected in type II en bloc resection of proximal fibula tumors. 8 In the present study, we found that malignancy rather than en bloc resection was a significant risk factor in the univariate analysis. In the multivariate analysis, neither malignancy nor en bloc resection was an independent risk factor for postoperative peroneal nerve palsy.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“… 1 , 10 In contrast, iatrogenic permanent loss of peroneal nerve function is expected in type II en bloc resection of proximal fibula tumors. 8 In the present study, we found that malignancy rather than en bloc resection was a significant risk factor in the univariate analysis. In the multivariate analysis, neither malignancy nor en bloc resection was an independent risk factor for postoperative peroneal nerve palsy.…”
Section: Discussionsupporting
confidence: 46%
“…Malignant potential, more invasive surgical treatments, huge tumor volumes, and some other factors are considered associated with a poorer prognosis; however, these factors appear to be interactive with one another, and their association with recurrence and postoperative complications have not been fully explored in contemporary studies. 3 , 4 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Zhao et al compared knee stability and MSTS functional scores of patients who underwent type I and type II en bloc proximal fibula resections. 11 According to their results, in patients who underwent LCL and biceps femoris tendon reconstruction surgery, higher rates of knee stability and MSTS scores were exhibited as compared to patients without reconstruction. Additionally, for type I resections, they reported a higher rate of knee stability in the reconstruction group, while no statistical difference was found for type II resections.…”
Section: Discussionmentioning
confidence: 99%
“…Although stability is not much disturbed even without reconstruction 19 but some studies recommend that the reconstruction of this ligament adds to the stability of the knee. 20 21 …”
Section: Discussionmentioning
confidence: 99%